The impact of motivation on student’s academic achievement and learning outcomes in mathematics among secondary school students in Nigeria (2007)
In our match towards scientific and technological advancement, we need nothing short of good performance in mathematics at all levels of schooling. In an effort to achieve this, this study investigated the impact of motivation on students’ school academic achievement in mathematics in secondary schools using motivation for academic preference scale (α = 0.82) as a measuring instrument and achievement test in mathematics (ATM) Two hypotheses were tested for significant at 0.05 margin of error using t-test and analysis of variance (ANOVA) Results showed that gender difference were significant when impact of motivation on academic achievement was compared in male and female students. Also, other result indicates significant difference when extent of motivation was taken as variable of interest on academic achievement in mathematics based on the degree of their motivation. Implications, suggestions and recommendations on students, parents, government, counsellors, educational stakeholders, etc were discussed.